Improving Corrosion Behavior of Chemically Bonded Phosphate Ceramic Coating Reinforce with GO-TiO2 Hybrid Material. (24th December 2021) - Bian, Da; Ni, Zifeng; Qian, Shanhua; Zhao, Yongwu
Abstract : To further enhance the corrosion resistance of chemically bonded phosphate ceramic coating, TiO2 was grafted on the surface of GO to enhance the interfacial adhesion between GO and the coating. SEM results show that the presence of TiO2 on GO creates a good interfacial adhesion between GO and the coating. In addition, EIS experiments were carried out to investigate the performance of the coatings on the corrosion resistance. The result indicates that the corrosion resistance is enhanced with the introduction of GO-TiO2 hybrid material. Beside of the influence of GO on the corrosion resistance, the good interfacial adhesion between GO and the coating with the presence of TiO2 hybrid material can consume more fracture energy to stop the crack propagation, which leads to the high corrosion resistance.